DIAGNOSTIC SIGNIFICANCE OF VASCULAR ENDOTHELIAL GROWTH FACTOR IN PATIENTS WITH PRIMARY MITRAL VALVE PROLAPSE - A. V. Yagoda; N. N. Gladkikh; Т. E. Zangelova (Кардиоваскулярная терапия и профилактика, 2017)
Aim. To evaluate diagnostic significance of the type A vascular endothelial growth factor (VEGF-A) and its receptors type 1 and 2 (VEGF-R1 and VEGF-R2) in primary mitral valve prolapse (MVP) patients.Material and methods. Totally, 83 MVP patients studied: 61 males, 22 females; mean age 21,93±4,22 y. o. The signs of systemic inflammation were assessed, as the grade of connective tissue involvement. Immune enzyme analysis was done for serum levels of VEGF-А, VEGF-R1 and VEGF-R2 (“Bender MedSystems GmbH”,Austria). Controls included 20 healthy volunteers — 14 males, 6 females, mean age 21,10±0,55 y. o. with no MVP and any other dysplastic features.Results. In the MVP group, the decreased levels of circulating VEGF-R1 were found, as the increase of cases number of high (42,17%) and low (32,53%) concentration of VEGF-А. In low levels of VEGF-A and VEGF-A/ VEGF-R1 prevalence of grade II mitral regurgitation increases 5,1 times comparing to the group of retained balance of VEGF-A and VEGF-R1 — 95% confidence interval (CI) 1,25-20,88, and the prevalence of clinically significant cardiac rhythm and conduction disorders increases 5,25 times in comparison to the cases with elevated VEGF-A and VEGF-R1 — 95% CI 1,33-20,76 and 4,09 times — comparing MVP patients with retained balance of VEGF-A and VEGF-R1 — 95% CI 1,18-14,17.Conclusion. In primary MVP patients, regardless clinical phenotype of monogenic hereditary syndromes, the heterogeneity of deviation and regulation of VEGF has been established. Highest number of II grade mitral regurgitation, significant rhythm disorders was found in the group with low VEGF-A and VEGF-A/VEGF-R1, that might be implemented as optimized risk stratification in heterogenic MVP patients population.